ANALYSIS OF FINANCIAL PERFORMANCE OF REGIONAL GENERAL SERVICES AGENCY (BLUD)(CASE STUDY IN THE REGIONAL TECHNICAL IMPLEMENTATION UNIT (UPTD) PAYUNGSARI COMMUNITY HEALTH CENTER (PUSKESMAS) PANUMBANGAN DISTRICT CIAMIS REGENCY PERIOD 2018 AND 2019) - Taufik Hermansyah; Lati Sari Dewi; Asep Saeful Falah (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2023)
The main problem in this study is the increase in realization, but it does not reach the predetermined budget in 2018 and 2019. The purpose of this study is to determine the financial performance of Puskesmas Payungsari after being designated as BLUD in 2018 and 2019. In its financial management, Puskesmas Payungsari must have constraints that are faced, problems regarding the budget are something that cannot be avoided. Sometimes high planning targets are not proportional to low budget realization or vice versa. This type of research is a case study. Data obtained by doing documentation. Quantitative descriptive data analysis techniques are used to measure financial performance based on financial ratios. The results show that the financial performance of Puskesmas Payungsari after being a BLUD in 2018 and 2019 is seen from measurements using financial ratios such as cash ratios, current ratios, accounts receivable collection period, asset turnover fixed, fixed assets consideration, equity compensation, inventory turnover, and the ratio of PNBP to operating expenses. From the calculation of these financial ratios, the total score fluctuates, from these results based on the Regulation of the Director General of Treasury NUMBER PER-36 / PB / 2016, it can be concluded that the financial performance of Puskesmas Payungsari in 2018 and 2019 is MEDIUM criteria in predicate B.